Epidemiological Overview of Implementation of the First Monthly Mini Workshop of Community Health Centers in Jeneponto Regency in 2024 - Amiluddin (Formosa Journal of Science and Technology, 2024)
Puskesmas is a place where promotive, preventive, curative and rehabilitative health efforts are carried out by the government, regional government and community. The main aim of this research is to obtain an epidemiological picture of the implementation of the first month of the Puskesmas Mini Workshop in Jeneponto Regency in 2024. This research uses a descriptive survey method. The results showed that 7 (35%) Community Health Centers carried out mini workshops (Lokmin) in the first month on time, 13 (65%) not on time, and 11 (55%) produced annual RPK, and 9 (45%) did not produce Annual RPK. 8 (40%) Puskesmas produce monthly RPKs, and 12 (60%) do not produce monthly RPKs. 2 (10%) Community Health Centers carry out the distribution of tasks for the target areas (Darbin), and 18 (90%). 7 (35%) community health centers produced a Proposed Activity Plan (RUK) for the coming year, while 13 (65%) did not produce a RUK for the coming year. 19 (95%) community health centers produced a Strategic Plan, while 1 (5%) did not produce a Strategic Plan. Therefore, policy makers must evaluate the head of the community health center as an additional position to assess the implementation of the main duties and functions. The head of the community health center pays more attention to the Puskesmas management cycle to increase the accuracy of the TPCB in accompanying the mini workshop. The RPK report and Decree of the Person in Charge of Darbin must be sent to the Health Service no later than the second week of January of the current year. using RUK as a source for Village and District Musrenbang proposals